Analisis Dimensi Teks pada Lirik Lagu "Tanpa Pamrih" Karya Feby Putri (Teori Analisis Wacana Kritis Teun A. Van Dijk) - Kehe Tola, Nurwelemci; Djuli, Labu; Djokaho, Margareta P. E (Jurnal Lazuardi, 2025)
The problem formulation in this research is how is the analysis of the critical discourse text dimension model by Teun A. Van Dijk found in the lyrics of the song "Tanpa Pamrih" by Feby Putri?, how is the analysis of the social cognition dimension of critical discourse model by Teun A. Van Dijk found in the lyrics of the song "Tanpa Pamrih" by Feby Putri?, how is the analysis of the social context dimension of critical discourse model by Teun A. Van Dijk found in the lyrics of the song "Tanpa Pamrih" by Feby Putri?. The purpose of this research is to describe the analysis of the critical discourse text dimension model by Teun A. Van Dijk in the lyrics of the song "Tanpa Pamrih" by Feby Putri, to describe the analysis of the social cognition dimension of critical discourse model by Teun A. Van Dijk in the lyrics of the song "Tanpa Pamrih" by Feby Putri, and to describe the analysis of the social context dimension of critical discourse model by Teun A. Van Dijk in the lyrics of the song "Tanpa Pamrih" by Feby Putri. The method used is discourse analysis. The object of this research is a critical discourse analysis of the song lyrics "Tanpa Pamrih" by Feby Putri (Teun A. Van Dijk's Theory). The process of qualitative data analysis is supported by qualitative descriptive methods using observation and transcription/note-taking techniques. The results of this study show the data obtained by the researcher as follows: there are three forms of analysis found in the song "Tanpa Pamrih," namely text dimension analysis, social cognition analysis, and social context analysis. The text dimension analysis includes three aspects: macro structure (thematic), superstructure (semantic), and micro structure (syntactic, stylistic, rhetorical). Social cognition analysis reveals Feby Purti's creative process in creating "Tanpa Pamrih." The expressions conveyed by Feby Putri through the song "Tanpa Pamrih" are emotions of sadness and regret. Social context analysis involves the background behind Feby Putri's creation of the song "Tanpa Pamrih," which includes her personal experiences and the values in the song "Tanpa Pamrih"thatcanimpactsociety.